Peran Bahasa Inggris dalam Upaya Membangun Nalar Sadar Wisata - Maricar, Farida; Subuh, Rahma Do; Rauf, Ramis (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Language development is critical in communication amongst groups since humans, as individuals with economic demands rely on one another. Language is also an important tool for character development. Individual qualities can be established through logical reasoning. Reason and language have a very intimate relationship. English is an international language used in practically every corner of the world to communicate between people from different origins. Furthermore, English has a significant association with the tourism industry. Not only must tourism actors or administrators be able to communicate in English, but they will also deal with tourism visitors, particularly foreign tourists, whether they like it or not. There is no doubt that tourism development must coincide with the development of suitable or qualified human resources for tourism management. Effective communication between visitors and tourism actors or managers, including local citizens, is critical to achieving sustainable tourism. As a result, those working in the tourism business must have excellent communication abilities.